Food Hygiene and Sanitation in Six Food Providers at University X, South Sumatra - Isnadi, Yul; Malaka, Tan; Dahlan, Hatta; Novrikasari, Novrikasari (Kesmas, 2018)
Food provider at university is one of places that needs to implement standards of food hygiene and sanitation (FHS). This study aimed to evaluate and analyze practices of FHS based on Regulation of Health Minister No. 1098 of 2003 and best practices in six food providers at University X. This study used mixed method evaluation with sequential explanatory design through two stages. Stage I was in forms of assessment on six food providers, food handlers and laboratory examination on food and beverage samples as well as on eating utensils. Stage II was in form of focus group discussion (FGD) to deepen findings at stage I. Results of this study showed that 100% of food providers had not yet met the government’s regulation. As much as 67% of eating utensils and 83% of food were contaminated with bacteria. Based on food handler examination results, 100% of food handlers were not yet to get medical checkups and training. FGD results indicated that findings at stage I were associated with a lack of knowledge among food handlers and the absence of special unit to oversee FHS at campus. In conclusion, six food providers in the study area have not met the regulation.